Diffusion tensor imaging in evaluating testicular injury after unilateral testicular torsion and detorsion in rat model: A preliminary study. (22nd February 2021) - He, Chengbin; Zhou, Xiaoxuan; Cheng, Jianmin; Qin, Le; Dong, Fenglei; Zhang, Rui; Chen, Bo; Hu, Hongjie
Abstract: Diffusion tensor imaging (DTI) is a functional magnetic resonance sequence based on the movement of water molecules. This study attempted to investigate the feasibility of DTI in evaluating testicular injury after testicular torsion and detorsion. Seventy‐two rats were randomly divided into the sham group, torsion group and detorsion group. The left testis in the sham group was brought out through a scrotal incision for 1 hr, and that of the torsion group was twisted 720 o clockwise for 1 hr and fixed to the scrotum, while the detorsion group was restored after being twisted 720° for 1 hr. Rats were further divided into four subgroups according to the set time, then performed DTI and histology analysis. The mean diffusion of the torsion and detorsion groups increased within 24 hr ( p <.01), while it in the detorsion‐1‐week‐group was lower than that in the detorsion‐24‐hr‐group ( p <.05). The fraction anisotropy of both experimental groups decreased in the acute phase ( p <.01), while that of the detorsion‐1‐week‐group increased ( p <.01). Cosentino score in both experimental groups showed an increasing trend ( p <.05). Besides, the spermatogenic ability of the detorsion‐1‐week‐group decreased ( p <.05). In conclusion, DTI was able to evaluate the injury after testicular torsion and detorsion.